Creatine supplementation during recovery from rapid body mass loss in wrestlers - Oopik, V.; Paasuke, M.; Timpmann, S.; Medijainen, L.; Ereline, J.; Gapeyeva, H.
The aim of the study was to test the hypothesis that creatine consumed during recovery from rapid weight loss modifying metabolism accelerates the restoration of body mass and physical performance capacity. Six well-trained wrestlers reduced their body mass by 4.8-5.3% in two series of experiments separated by one month. During 17 h recovery, however, they consumed controlled diet supplemented in random order with 320 g of glucose (GL) or 320 g of glucose plus 30 g of creatine (CR). The subjects performed variable intensity test exercise at the Cybex II device before (T1) and after (T2) body mass loss and after the recovery (T3) on both trials. The test consisted of submaximal isokinetic knee extensions at an angular velocity of 1.57 rad _ s-1 for 45 s at the rate of 30 contractions each min (submaximal intensity work, Wsmax) followed by 15 s maximal effort (maximal intensity work, Wmax). Total duration of the test was 5 min. The concentration of ammonia and lactate was measured in blood obtained at rest and after cessation of each test exercise. The mean loss and regain of body mass was 3.9 kg and 2.4 kg on GL, 3.4 kg and 2.3 kg on CR trial. Wmax performed in T3 was 88.5% and 97.9% of that done in T1 on GL and CR trial, respectively (paired t-test P>0.05). However, during the 2nd minute of the test Wmax in T3 was (by 15.3%, P< 0.05) greater than in T2 on CR but not on GL trial. There was a decrease in blood ammonia accumulation in T3 in comparison to T2 on GL and CR trial by 56.9% (P< 0.05) and 34.9% (P>0.05), respectively. A significant increase in blood lactate level which did not differ between trials and was similar in T1, T2 and T3 occurred as a result of each test exercise. These results suggest that creatine supplementation during 17 h recovery from rapid body mass loss does not accelerate the restoration of body mass but still has positive influence on physical performance capacity in wrestlers.